The Testing of Accounting Information in The Market Concerning Earning Management on The Index Mining Companies - Reza ade cellia; Pujiono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Abstrak. This research aimed to examine the benefits of accounting information in the form of earnings management on investment decisions. Company value is one of the benchmarks for making investment decisions. Company value can be seen from share price fluctuations. The type of research used was a quantitative approach using secondary data. The objects of this research were mining sector companies listed on the IDX for the 2015-2020 period. This research applied a modified Jones model to calculate earnings management. The data needed in this research were financial reports and company share prices. The sampling technique used was purposive sampling with multiple linear regression data analysis techniques. The research result showed that earnings management influences stock prices. Thus, this research can be used by investors as information for making investment decisions. Keywords: earning management, mining, modified Jones model, stock prices